How to Prevent Unhelpful Personality Traits from Evolving into Unhelpful Financial Behaviors: The Benefits of Future Clarity - Simon Andrew Moss; Eraj Ghafoori; Liam Smith (Journal of Financial Therapy, 2018)
Many organizations have implemented programs to improve the financial behavior of impending retirees and other vulnerable demographics. These programs are predicated on the assumption that financial behavior is indeed modifiable. Yet, many enduring traits, such as emotional instability, could promote financial anxiety and provoke imprudent financial behaviors, limiting the utility of these programs. This study, however, tests the possibility that future clarity—the degree to which individuals perceive their future as vivid and certain—could diminish the extent to which emotional instability coincides with financial anxiety and imprudent financial behavior. Specifically, 1516 participants over 50 completed a questionnaire that gauges emotional instability, future clarity, financial anxiety, and financial behaviors. Future clarity did indeed diminish the extent to which emotional stability was related to financial anxiety but not financial behavior. Thus, programs that are designed to improve financial literacy should also help individuals clarify how to reach their future aspirations.
Keywords: emotional instability; financial anxiety; financial behavior; future clarity; personality.